2018
DOI: 10.1371/journal.pone.0195101
|View full text |Cite
|
Sign up to set email alerts
|

Medications and pregnancy: The role of community pharmacists – A descriptive study

Abstract: BackgroundSafe use of medications during pregnancy requires a comprehensive understanding of risk-benefit profiles for individual treatments. Pharmacists are supported in this aspect by clinical information agencies (e.g. MotherSafe, a telephone-based teratogen information service) and reference texts. To what extent and for what reasons Australian pharmacists utilise these services/resources are yet unknown. Further, debate on replacement of conventionally defined medication safety in pregnancy categories (A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
2
36
0
1
Order By: Relevance
“…Almost twice as many patients sought more advice regarding medications with risk category A compared to pharmacists themselves. Although in general, clinical hesitancy about counselling pregnant women about drugs was subliminally evident in a previous qualitative study with Australian pharmacists, pharmacists in the study still appeared reasonably confident in counselling women about drugs in categories A, D and X, where they probably felt the evidence supporting the allocation of that particular category was straightforward . Analysis of MotherSafe calls in this study reinforced this finding regarding pharmacists’ confidence in counselling about drugs in category A.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Almost twice as many patients sought more advice regarding medications with risk category A compared to pharmacists themselves. Although in general, clinical hesitancy about counselling pregnant women about drugs was subliminally evident in a previous qualitative study with Australian pharmacists, pharmacists in the study still appeared reasonably confident in counselling women about drugs in categories A, D and X, where they probably felt the evidence supporting the allocation of that particular category was straightforward . Analysis of MotherSafe calls in this study reinforced this finding regarding pharmacists’ confidence in counselling about drugs in category A.…”
Section: Discussionsupporting
confidence: 54%
“…Although pharmacists profess a need for succinct information, the A–X categorisation of drugs in pregnancy should not be used as the definitive resource in prescribing medications in pregnancy, for women planning to conceive or those breastfeeding, as categories do not apply to the latter. However, unfortunately, pharmacists rely heavily upon the letter categories (which are included in prescribing references as well as in product and consumer medicines information) when managing pregnant patients . Misuse of categories can result in significant harm including undue anxiety due to heightened perception of risk and cessation of needed medications on supposed fetal safety grounds, thereby potentially compromising both the mother's and baby's health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can prevent medication misuse and prevent patients from potentially seeking information from unreliable sources. If a patient is initiated on a teratogenic medication while hospitalized, an inpatient clinical pharmacist can assist in counseling the patient regarding the risks and benefits of the medication as well as appropriate contraceptive use to prevent pregnancy [49]. Advanced drug-pregnancy alerts can be implemented by organizations to alert inpatient pharmacists when hospitalized patients may be or are pregnant, and these may be particularly helpful when deciding whether to initiate teratogenic medications.…”
Section: Counseling On Contraception When Initiating Teratogenic Medimentioning
confidence: 99%
“…The International Pharmaceutical Federation Council (2011) approved an article about the role of the pharmacist to deal with the special population which states guidelines on Good Pharmacy Practice to ameliorate the health of pregnant and lactating women [13]. Many studies are carried out to define the role of community pharmacists to deal with special population sickness in USA, Canada, Iceland, Kuwait, Norway, Thailand, Uganda, and Qatar [14][15][16][17][18]. Most of these studies evaluated the pharmacist's responses to treat symptoms observed during pregnancy and lactation to advice and counsel the special population along with their recommendations and knowledge about medications.…”
Section: Introductionmentioning
confidence: 99%